2021
DOI: 10.1007/s12517-021-07873-y
|View full text |Cite
|
Sign up to set email alerts
|

Estimating snow density, depth, volume, and snow water equivalent with InSAR data in the Erciyes mountain/Turkey

Abstract: In this study, it is aimed to calculate snow density, depth, and snow water equivalent with the help of single polarization TerraSAR-X data. In this context, Mount Erciyes/Turkey was chosen as the pilot study area and TerraSAR-X data with HH polarization were used. In addition, in situ measurements were performed simultaneously with the satellite pass to be used as input and validation data for the model to be used. Also, snow densities were obtained by inverse approach, Kriging, and ISO-4355 methods. Snow den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…For example, Yang & Li (2021) assimilated snow depth from differential InSAR data, ultrasonic detectors, and field survey using ensemble Kalman filter. Torun and Ekercin (2021) calculated and verified the snow density, depth, and snow water equivalent in the Mount Erciyes (Turkey) using the HH single polarization SAR data. However, SAR amplitude and coherence have rarely been used to estimate the snow depth.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yang & Li (2021) assimilated snow depth from differential InSAR data, ultrasonic detectors, and field survey using ensemble Kalman filter. Torun and Ekercin (2021) calculated and verified the snow density, depth, and snow water equivalent in the Mount Erciyes (Turkey) using the HH single polarization SAR data. However, SAR amplitude and coherence have rarely been used to estimate the snow depth.…”
Section: Introductionmentioning
confidence: 99%
“…The transferability of such an approach to the spaceborne case has been already assessed in several studies [25], [26], [27], [28]. Some of which showed that the revisit time of current missions is one of the main limiting factors, as well as the lack of validation data.…”
mentioning
confidence: 99%